Partisan Discrimination in Hiring - Martin Abel; Andrea Robbett; Daniel F. Stone (Institute of Labor Economics (IZA), 2024)
This study experimentally investigates the role of politics in hiring decisions. Participants acted as employers, determining the highest wage to offer candidates based only on their demographic characteristics, education, and partisanship. We find that both Democratic and Republican participants significantly favor co-partisans, with an out-partisan wage penalty of 7.5%. Discrimination is consistent across tasks that focus respectively on competence, shirking, feedback responsiveness, and voluntary effort, and appears largely driven by biased beliefs about partisan productivity, while affective polarization is also predictive of the out-partisan wage penalty. Discrimination does not increase in a treatment where workers benefit financially from being hired.
Keywords: J70; D90; C91; 330; discrimination; affective polarization; inaccurate beliefs